Investigation of fascial treatment effectiveness on pain, flexibility, functional level, and kinesiophobia in patients with chronic low back pain - Endamlı, Doğan Burak; Bayramlar, Kezban Yigiter; Turhan, Begümhan (University School of Physical Education in Wrocław, 2019)
Introduction. Fascial manipulations have received attention in the treatment of chronic low back pain (CLBP). The purpose of this study is to investigate the effectiveness of fascial manipulation on pain, flexibility, functional level, and kinesiophobia in patients with CLBP. Methods. overall, 55 individuals with a history of CLBP, without neurological deficits, lumbar disc herniation, lumbarization, spondylosis, or lumbar surgical history were included in the study. The participants were randomly divided into 2 groups depending on the patient protocol numbers. Subjects with odd protocol numbers were assigned to the study group (fascial manipulation) and those with even numbers to the control group (conventional physiotherapy). Both groups were assessed before and after the treatment in terms of pain, flexibility, functional level, and kinesiophobia. Results. There were significant differences after both treatment methods in terms of pain, functional level, and flexibility (p < 0.05). However, pain levels decreased more statistically significantly in the fascial manipulation group than in the control group (p < 0.05). No significant difference was observed between the groups in terms of functional level, flexibility, or kinesiophobia after the treatment (p > 0.05). Conclusions. We stated that fascial manipulation was more effective on pain than conventional physiotherapy methods (hot pack, microwave diathermy, interferential flow-vacuum applications, posterior pelvic tilt and abdominal exercises, stretching hip flexors and lumbar extensors) in patients with CLBP. © University School of Physical Education in Wrocław
Keywords: Fascia; Fascial manipulation; Low back pain